Developing public-private partnerships in Liberia - Kaplan, Zachary (World Bank studies., 2012)
Liberia is making great strides to recover from its recent era of conflict and reestablish itself as a global competitor. Central to Liberia's economic growth is its rich endowment of natural resource such as iron ore and rubber. Liberia's natural resources have defined, in large part, the country's engagement with the private sector. However, the Government of Liberia is now exploring new ways to partner with the private sector with the objective of growing the economy. One method is by developing public-private partnerships (PPPs) in core infrastructure and social services. This Study examin.